2014
DOI: 10.12691/ajssm-2-5a-1
|View full text |Cite
|
Sign up to set email alerts
|

Relevance and Incidence of Musculoskeletal Injuries in Indian Tennis Players; an Epidemiological Study

Abstract: Professional tennis sports involve powerful movements repeatedly subjecting the musculoskeletal system to heavy mechanical load, thereby increasing risk for most acute and overuse injuries. Despite many researches in sports injuries, however, none of them has dealt with prevalence, incidence, and pattern of tennis injuries among Indian tennis players. The aim of this study was to prospectively make a survey of prevalence and incidence of musculoskeletal injuries in Indian tennis players. A convenience sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…Tennis is a popular sport globally with participants from different age groups participating in more than 200 countries affiliated with the International Tennis Federation (Kachanathu, Kumar & Malhotra 2014 ). Tennis is characterised by repeated, explosive motions and the involvement of several muscle groups during different strokes, which fluctuate randomly from brief periods of maximal or near maximal work to longer periods of moderate and low intensity activity (Arora & Doshi 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tennis is a popular sport globally with participants from different age groups participating in more than 200 countries affiliated with the International Tennis Federation (Kachanathu, Kumar & Malhotra 2014 ). Tennis is characterised by repeated, explosive motions and the involvement of several muscle groups during different strokes, which fluctuate randomly from brief periods of maximal or near maximal work to longer periods of moderate and low intensity activity (Arora & Doshi 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The weight of the racquet can also contribute to wrist injuries if not suitable to the tennis player (Martin et al 2014 ). Player-specific factors, such as age, sex, volume of play, skill level, racquet properties and grip positions as well as the playing surface are some of the risk factors that can predispose a tennis player to injury (Kachanathu et al 2014 ). Muscle strain is one of the most common injuries in tennis (Kazemi, Rahnama & Alizadeh 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to many authors, the most common injury observed in tennis athletes occurs in the elbow. Kachanathu et al [7] saw that the most acute injuries occurred in the body joints, such as in the elbows, followed by wrists, ankles, shoulders, and knees. They also observed that lateral epicondylitis (tennis elbow) occurs more frequently in recreational rather than in professional tennis athletes.…”
Section: Introductionmentioning
confidence: 99%
“…En el caso concreto de tenistas en edad adolescente, debemos considerar en primer lugar que las lesiones más comunes son las que se generan a través de microtraumatismos repetitivos (Ben Kiblera & Safranb, 2005). De todas ellas, las que afectan al hombro son relativamente frecuentes, hasta el punto de que algunos estudios sitúan su nivel de incidencia en un 14.8% (Sansiseña & Rueda, 2011).…”
Section: Introductionunclassified
“…In the specific case of adolescent tennis players, we should first consider that the most common injuries are those caused by repetitive micro-injuries (Ben Kiblera & Safranb, 2005). Of all of them, those affecting the shoulder are relatively frequent; indeed, some studies situate their frequency at 14.8% (Sansiseña & Rueda, 2011).…”
Section: Introductionmentioning
confidence: 99%